Folliculotropic mycosis fungoides. (4th May 2018) - Mitteldorf, Christina; Stadler, Rudolf; Sander, Christian A.; Kempf, Werner
Summary: Accepted by the WHO and EORTC as a variant of classic mycosis fungoides, folliculotropic (syn.: follicular or pilotropic) mycosis fungoides (FMF) is characterized by a broad clinical and histological spectrum with numerous differential diagnoses. Recent studies have shown that FMF can be divided into two prognostically different subgroups, both marked by histological as well as clinical differences. Treatment should therefore be tailored to the various subtypes and clinical courses. The present review highlights the clinical and histological manifestations of FMF as well as the new subclassification. Moreover, important differential diagnoses and therapeutic options are discussed.